2010
DOI: 10.1007/s10047-010-0513-0
|View full text |Cite
|
Sign up to set email alerts
|

Crisis in the operating room: fires, explosions and electrical accidents

Abstract: Fires, explosions and electrical accidents in the operating theater are rare events, but are devastating in terms of structural damage to the equipment in theaters and to human lives. While various circumstances lead to these troubles, we can avoid and manage them by learning from the instructive cases accumulated so far. We describe operating room crises such as fires, explosions and electrical breakdowns, and discuss causes and countermeasures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
1
9
0
6
Order By: Relevance
“…20 The most common types of power failure events identified in this study are those where backup generators did not restore power as expected, or power returned, but took additional time for computers and monitors to "reboot." The findings of this study mirror Nishiyama et al 21 and others 2,13 who found that the 3 most common types of power failure are main electrical failure and generator shutdown, generator power surge, and failure of the backup generator or the uninterrupted power supply.…”
Section: Discussionsupporting
confidence: 87%
“…20 The most common types of power failure events identified in this study are those where backup generators did not restore power as expected, or power returned, but took additional time for computers and monitors to "reboot." The findings of this study mirror Nishiyama et al 21 and others 2,13 who found that the 3 most common types of power failure are main electrical failure and generator shutdown, generator power surge, and failure of the backup generator or the uninterrupted power supply.…”
Section: Discussionsupporting
confidence: 87%
“…If the heart is contracting when the pump stops, only the occlusion of the venous line may restore systemic perfusion, sometimes with the help of inotropic support. If the aorta is clamped, the only solution is hand-cranking [ 1 , 2 , 4 , 5 ]. Hand-cranking is effective in terms of restoring systemic perfusion, but the universally accepted time limit for a single person is 15 minutes, to prevent exhaustion [ 1 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…During 2000 routine CPB cases in our institution within the period of 4 years, 1 case of electrical failure was observed. Different mechanisms of electrical failure have been reported, including mains failure, generator failure, and uninterrupted power supply (UPS) failure [ 1 , 2 ]. Since these kinds of equipment failure and accidents are very rare, little attention is given to preventative measures concerning electrical supply and backup batteries.…”
Section: Introductionmentioning
confidence: 99%
“…In the third subcategory, the patient is definitely involved by the error event with no possibilities of involvement of the surrounding personnel and structures by the same event. Other authors have separately discussed these events, but without sufficient classifications [4,11]. …”
Section: Discussionmentioning
confidence: 99%
“…The term “surgical fires” mainly refers to fires ignited within the operative room in the presence of the surgical fire triangle: ignition source, fuel, and oxygen. However, it could be a broader subject that has different varieties of thermal and electrical injuries in the operative theater including accidents of fires, explosions, burns, and electrocutions [4]. The risks are not only directed towards the patients, but they may also extend to the medical staff and co-workers.…”
Section: Introductionmentioning
confidence: 99%